Astrocytic transforming growth factor‐beta signaling reduces subacute neuroinflammation after stroke in mice. Issue 8 (18th June 2014) - Cekanaviciute, Egle; Fathali, Nancy; Doyle, Kristian P.; Williams, Aaron M.; Han, Jullet; Buckwalter, Marion S.
Abstract : Astrocytes limit inflammation after CNS injury, at least partially by physically containing it within an astrocytic scar at the injury border. We report here that astrocytic transforming growth factor‐beta (TGFβ) signaling is a second, distinct mechanism that astrocytes utilize to limit neuroinflammation. TGFβs are anti‐inflammatory and neuroprotective cytokines that are upregulated subacutely after stroke, during a clinically accessible time window. We have previously demonstrated that TGFβs signal to astrocytes, neurons and microglia in the stroke border days after stroke. To investigate whether TGFβ affects astrocyte immunoregulatory functions, we engineered "Ast‐Tbr2DN" mice where TGFβ signaling is inhibited specifically in astrocytes. Despite having a similar infarct size to wildtype controls, Ast‐Tbr2DN mice exhibited significantly more neuroinflammation during the subacute period after distal middle cerebral occlusion (dMCAO) stroke. The peri‐infarct cortex of Ast‐Tbr2DN mice contained over 60% more activated CD11b + monocytic cells and twice as much immunostaining for the activated microglia and macrophage marker CD68 than controls. Astrocytic scarring was not altered in Ast‐Tbr2DN mice. However, Ast‐Tbr2DN mice were unable to upregulate TGF‐β1 and its activator thrombospondin‐1 2 days after dMCAO. As a result, the normal upregulation of peri‐infarct TGFβ signaling was blunted in Ast‐Tbr2DN mice. In this setting of lower TGFβ signaling and excessive neuroinflammation, we observed worse motor outcomes and late infarct expansion after photothrombotic motor cortex stroke. Taken together, these data demonstrate that TGFβ signaling is a molecular mechanism by which astrocytes limit neuroinflammation, activate TGFβ in the peri‐infarct cortex and preserve brain function during the subacute period after stroke. GLIA 2014;62:1227–1240 Main points: Astrocytic TGFβ signaling is a critical pathway for limiting subacute neuroinflammation in peri‐infarct cortex after stroke. Mice with inhibited astrocytic TGFβ signaling exhibited excessive neuroinflammation, failed to upregulate TGFβ, and developed worse motor deficits after stroke.